Próba budowy modelu geologicznego pradoliny głogowsko-barudzkiej w okolicy Nowej Soli z wykorzystaniem sztucznych sieci neuronowych = Geological model test construction of great-valley Głogów in area a Nowa Sól with the use of neural networks - Kraiński, Andrzej; Mrówczyńska, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article attempts to determine the course of geological strata for a great-valley area Głogów, using the multilayer neural network the sigmoidal type training by back propagation method, which is based on the known theory of gradient optimization methods. Determination of the experience of individual layers was made on the basis of the coordinates (x,y), and data in the form of ceiling height, depth and thickness of floor obtained from field studies.
Keywords: pradolina; depresja glacitektoniczna; sztuczne siecineuronowe; gradientowe metody optymalizacji; neural networks; gradient methods of optimalization; great-valley; glacitectonic depression